Bhagavatī ārādhanā - Śivakōtyācārya (Jīvarāja Jaina granthamālā. Hindī Vibhāga, 1978)
Verse work, with a classical commentary, on ascetic fundamentals according to the Yāpanīya school of Jainism; critical edition.